Ethnic Characteristics of Students' Value Orientations - E Ju Chebotareva (Peoples' Friendship University of Russia (RUDN University), 2012)
The article is devoted to the ethnic features of value orientations in students from different parts of the world. It is shown that the lives of the students from Latin America and Central Asia are more holistic and meaningful than the lives of the students from China, the Middle East and Russia. Latin American students are more focused on individuality, self-regulation, and the Central Asian - on collectivism, the controllability of life events. The gender specifics of the value orientations of students are described. The connection between the students' value orientations personality components such as a basic trust in the world, social and emotional intelligence, ethnic identity and tolerance towards the people of other ethnic groups, stress-coping strategies are analyzed.